Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Geometri Analitik Materi Persamaan Garis berdasarkan Teori Newman - Hendrika Bete; Justin Eduardo Simarmata; Maria Naimnule (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
Geometry is an axiomatic system and a collection of generalizations, models, and evidence about the forms of objects, planes, and space. Geometry is a branch of mathematics and is very important for students in mathematics education study programs. However, student learning outcomes that do not meet expectations cause problems. The problem is the low grades of students in the second semester based on the exam results. It happens because of the weak mastery of the material, and students still need help solving math problems. This study aimed to determine the types of student errors in solving geometry problems in line equations. The results of this study are that there are reading errors, that there are students who find it difficult to identify the questions, do not know what is known and are asked in the questions; misunderstand the problem (comprehension), that the student is not able to understand the information on the question; transformation errors, that students cannot convert information into correct mathematical sentences; process skills, that students not being able to apply the calculation steps correctly and not being thorough in solving problems; and writing errors (encoding), that students write the incorrect conclusions. This type of research is descriptive research using a qualitative approach.